Graphene and Nanowire Transistors for Cellular Interfaces and Electrical Recording - Cohen-Karni, Tzahi (2010)
Nanowire field-effect transistors (NW-FETs) have been shown to be powerful building blocks for nanoscale bioelectronic interfaces with cells and tissue due to their excellent sensitivity and their capability to form strongly coupled interfaces with cell membranes. Graphene has also been shown to be an attractive building block for nanoscale electronic devices, although little is known about its interfaces with cells and tissue. Here we report the first studies of graphene field effect transistors (Gra-FETs) as well as combined Gra- and NW-FETs interfaced to electrogenic cells. Gra-FET conductance signals recorded from spontaneously beating embryonic chicken cardiomyocytes yield well-defined extracellular signals with signal-to-noise ratio routinely >4. The conductance signal amplitude was tuned by varying the Gra-FET working region through changes in water gate potential, V(wg). Signals recorded from cardiomyocytes for different V(wg) result in constant calibrated extracellular voltage, indicating a robust graphene/cell interface. Significantly, variations in V(wg) across the Dirac point demonstrate the expected signal polarity flip, thus allowing, for the first time, both n- and p-type recording to be achieved from the same Gra-FET simply by offsetting V(wg). In addition, comparisons of peak-to-peak recorded signal widths made as a function of Gra-FET device sizes and versus NW-FETs allowed an assessment of relative resolution in extracellular recording. Specifically, peak-to-peak widths increased with the area of Gra-FET devices, indicating an averaged signal from different points across the outer membrane of the beating cells. One-dimensional silicon NW- FETs incorporated side by side with the two-dimensional Gra-FET devices further highlighted limits in both temporal resolution and multiplexed measurements from the same cell for the different types of devices. The distinct and complementary capabilities of Gra- and NW-FETs could open up unique opportunities in the field of bioelectronics in the future.